2001
DOI: 10.1053/jlts.2001.23010
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to influenza vaccine in adult liver transplant recipients

Abstract: Influenza virus infection may cause significant complications in liver transplant recipients, and whether vaccination is effective in these patients is controversial. We performed a study to assess the immune response to influenza vaccine in liver transplant recipients and patients with cirrhosis compared with healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 6 publications
2
31
1
Order By: Relevance
“…Previous studies of antibody seroconversion after influenza vaccination ranged from 15%-95% in liver transplant recipients and 56%-100% in healthy controls to the three influenza virus strains (3)(4)10). In a study of 264 health care professionals, overall vaccine response was noted in 57% (41%-78%) of the subjects for the A (H3N2) and in 40% (33%-52%) of subjects for influenza B vaccine (11).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies of antibody seroconversion after influenza vaccination ranged from 15%-95% in liver transplant recipients and 56%-100% in healthy controls to the three influenza virus strains (3)(4)10). In a study of 264 health care professionals, overall vaccine response was noted in 57% (41%-78%) of the subjects for the A (H3N2) and in 40% (33%-52%) of subjects for influenza B vaccine (11).…”
Section: Discussionmentioning
confidence: 97%
“…Influenza vaccination has reduced the morbidity and perhaps mortality from influenza virus infection in cirrhotic and post liver transplant patients. Several studies have demonstrated acceptable levels of protective postimmunization antibody titers being achieved post liver transplantation (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Among persons with kidney or heart transplants, seroresponse rates were similar or slightly reduced compared with healthy persons (232)(233)(234)(235)(236)(237). However, a small study involving participants with liver transplants indicated a reduced immunologic response to influenza vaccinations (238). Response rates were lowest if vaccination occurred within the four months after the transplant procedure (239).…”
Section: Immunocompromised Personsmentioning
confidence: 99%
“…Data in adult liver transplant recipients are also controver-sial (31,75,77). We recently found that liver recipients had an impaired immune response to the A/Sidney/H3N3 antigen of the 1999 to 2000 trivalent vaccine compared to controls (31).…”
Section: Influenza Vaccinementioning
confidence: 99%